2018
DOI: 10.1016/j.matlet.2018.03.089
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponse of KNbO3–AFeO3 (A = Bi3+ or La3+) ceramics and its relationship with bandgap narrowing

Abstract: The crystal structure of (1-x)KNbO3-xBiFeO3 (KNBF) and (1-x)KNbO3-LaFeO3 (KNLF) (where x=0.00; 0.01; 0.02; 0.04; 0.08; 0.16; 0.32) was evaluated by XRD and Raman spectroscopy. XRD data show the crystal symmetry to evolve from orthorhombic to tetragonal with increasing x. The optical bandgap was found to narrow systematically with increasing x. Raman spectroscopy analysis corroborated long-range polar order in all compositions. The photoresponse of x=0.32 shows a typical diode-like behaviour, with current and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Nevertheless, these Ni induced intermediate energy levels can enhance the overall optical absorption. Grinberg et al (2013) measured a modest short-circuit photocurrent, J sc , of 0.1 µA.cm −2 and open-circuit photovoltage, Subsequently, Elicker et al (2018) also found a similar degree of bandgap narrowing (i.e., a 0.9-1 eV) in the K 1−x La x Nb 1−x Fe x O 3 (KNLF) system, suggesting that the electronic lone-pair in Bi 3+ may play a negligible role in the physics of bandgap narrowing of KN, as shown on Table 5. These researchers fabricated FEPV devices from KNBF and KNLF (x = 0.32), which combined with a redox couple (I − /I 3− ) exhibited a typical diode-like behavior, showing J sc and V oc values of 0.115 µA and 0.075 V for KNBF and 0.19 µA (Grinberg et al, 2013) 3.1 (direct) (Zhou et al, 2014) BaCo 1/2 Nb 1/2 O 3−x (x = 0.4) 2.4 (direct) (Yu et al, 2016) BaCo 1/3 Nb 2/3 O 3 (x = 0.25) 2.44 (direct) (Si et al, 2018) BaNb 1/2 Fe 1/2 O 3−x (x = 0.1) 2.48 (direct) and 0.035 V for KNLF, respectively.…”
Section: Impact Of Doping On the Bandgap Of Knmentioning
confidence: 99%
“…Nevertheless, these Ni induced intermediate energy levels can enhance the overall optical absorption. Grinberg et al (2013) measured a modest short-circuit photocurrent, J sc , of 0.1 µA.cm −2 and open-circuit photovoltage, Subsequently, Elicker et al (2018) also found a similar degree of bandgap narrowing (i.e., a 0.9-1 eV) in the K 1−x La x Nb 1−x Fe x O 3 (KNLF) system, suggesting that the electronic lone-pair in Bi 3+ may play a negligible role in the physics of bandgap narrowing of KN, as shown on Table 5. These researchers fabricated FEPV devices from KNBF and KNLF (x = 0.32), which combined with a redox couple (I − /I 3− ) exhibited a typical diode-like behavior, showing J sc and V oc values of 0.115 µA and 0.075 V for KNBF and 0.19 µA (Grinberg et al, 2013) 3.1 (direct) (Zhou et al, 2014) BaCo 1/2 Nb 1/2 O 3−x (x = 0.4) 2.4 (direct) (Yu et al, 2016) BaCo 1/3 Nb 2/3 O 3 (x = 0.25) 2.44 (direct) (Si et al, 2018) BaNb 1/2 Fe 1/2 O 3−x (x = 0.1) 2.48 (direct) and 0.035 V for KNLF, respectively.…”
Section: Impact Of Doping On the Bandgap Of Knmentioning
confidence: 99%
“…Currently, most oxide ferroelectric ceramics manifest low J sc in the order of nA/cm 2 (1–200 nA/cm 2 ). A summary of the literature data for these systems is provided in Figure c. , Evidently, increasing the J sc of ferroelectric ceramics is critical for practical photovoltaic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Schematic diagram of enhanced J sc of KN-based semiconducting ferroelectric ceramics through Mn/Mg modification, bandgap engineering, and high-field poling. Bandgaps of (a) pure KN and (b) (1 – x )­KN- x MM ( x = 0.02, 0.04, 0.06, and 0.08) ceramics; (c) comparison of J sc of unpoled/poled (1 – x )­KN- x MM samples with other perovskite oxide-based photovoltaic devices; , , (d) ordered transformation of ferroelectric domains induced by high-field poling; and (e) steady-state photocurrent experiments of the poled/unpoled 0.94KN-0.06MM sample. Insets in (a) and (b) represent the P - E loops of pure KN and (1 – x )­KN- x MM ceramics, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…12 Similar reports of solid solutions of KNO with BaFe1/2Nb1/2O3, BaCo1/2Nb1/2O3-δ, BiYbO3, and LaFeO3 showed that the bandgap could be shifted down to 1.7 eV, 2.4 eV and 2.2 eV, 2.6 eV, respectively. [13][14][15][16] At last, several studies have focused on bandgap engineering by chemical substitution. Among those, reports on substitutions on the A-site of the perovskite showed a minor effect on the bandgap value.…”
Section: Introductionmentioning
confidence: 99%